A novel color change mechanism for breast cancer biomarker detection: naphthoquinones as specific ligands of human arylamine N-acetyltransferase 1 - Laurieri, N; Egleton, J; Varney, A; Thinnes, C; Quevedo, C; Seden, P; Thompson, S; Rodrigues-Lima, F; Dairou, J; Dupret, J; Russell, A; Sim, E (Public Library of Science, 2013)
Human arylamine N-acetyltransferase 1 (hNAT1) has become an attractive potential biomarker for estrogen-receptor-positive breast cancers. We describe here the mechanism of action of a selective non-covalent colorimetric biosensor for the recognition of hNAT1 and its murine homologue, mNat2, over their respective isoenzymes, leading to new opportunities in diagnosis. On interaction with the enzyme, the naphthoquinone probe undergoes an instantaneous and striking visible color change from red to blue. Spectroscopic, chemical, molecular modelling and biochemical studies reported here show that the color change is mediated by selective recognition between the conjugate base of the sulfonamide group within the probe and the conjugate acid of the arginine residue within the active site of both hNAT1 and mNat2. This represents a new mechanism for selective biomarker sensing and may be exploited as a general approach to the specific detection of biomarkers in disease.